CONSERVATION PARTNERSHIP IMPLEMENTATION BETWEEN RURAL FORESTRY EXTENSION CENTERS AND KELIMUTU NATIONAL PARK - Putri, Saprita Nuary Putri; Purnama, Maria M.E; Pramatana, Fadlan; Kaho, Ludji Michael Riwu (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Wologai Central Village conservation partnership was formed to deal with the increasing spread of invasive Kirinyuh plants in the Kelimutu National Park (KNP) area. This conservation partnership was created in the context of ecosystem recovery with an alternative program in the form of community empowerment around the site through an ecotourism management program. The Wologai Central Village Conservation Partnership aims to improve people's welfare and preserve conservation areas. Still, the management of the Wologai Central Village conservation partnership in the past five years has not shown optimal results for its formation in the control of the KNP area and the management of existing ecotourism. This study aims to determine the implementation of the ongoing conservation partnership between KNP and Sentra Penyuluhan Kehutanan Pedesaan (SPKP, Rural Forestry Extension Centers) in Wologai Central Village using data collection techniques, including interviews, observation, and documentation, which are then analyzed descriptively. The results showed that the Wologai Central Village conservation partnership had been appropriately implemented but had not yielded optimal results. In the